2024
DOI: 10.1021/acs.jafc.4c00747
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Prevents Against Ethanol-Induced Intestinal Barrier Dysfunction and NLRP3 Inflammasome Activation via NF-κB/MAPK Signaling Pathways in Mice and Caco-2 Cells

Yanan Zhao,
Bin Li,
Jiang Liu
et al.

Abstract: The potential of natural phytochemicals in addressing ethanol-related public safety concerns has been garnering attention. Galangin, a potent flavonoid renowned for its antioxidative and anti-inflammatory characteristics, is derived from the galanga plant, and propolis is derived from bees. Here, we documented the effects of galangin on ethanol-stimulated intestinal tight junction damage and investigated its potential protective mechanism in both in vivo and in vitro models, which has not been extensively inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These data provided some evidence that ROS were involved in 3-MCPD-induced NLRP3 activation. NLRP3 inflammasome assembly resulted in Caspase-1 activation, which induced the maturation and release of IL-1β and IL-18, as well as the cleavage of GSDMD into GSDMD-N, thereby promoting cellular pyroptosis. , We found that the NLRP3 inhibitor MCC950 inhibited 3-MCPD-induced pyroptosis. Thus, the results above implied that 3-MCPD suppressed mitophagy, resulting in a continuous accumulation of ROS, which activated NLRP3 and ultimately triggered pyroptosis.…”
Section: Discussionmentioning
confidence: 63%
“…These data provided some evidence that ROS were involved in 3-MCPD-induced NLRP3 activation. NLRP3 inflammasome assembly resulted in Caspase-1 activation, which induced the maturation and release of IL-1β and IL-18, as well as the cleavage of GSDMD into GSDMD-N, thereby promoting cellular pyroptosis. , We found that the NLRP3 inhibitor MCC950 inhibited 3-MCPD-induced pyroptosis. Thus, the results above implied that 3-MCPD suppressed mitophagy, resulting in a continuous accumulation of ROS, which activated NLRP3 and ultimately triggered pyroptosis.…”
Section: Discussionmentioning
confidence: 63%
“…The monolayer's integrity was monitored using the transepithelial electrical resistance (TEER), which was measured using a Millicell-ERS electrode. In the current investigation, a monolayer with TEER measured between 500 and 750 Ω cm 2 that was collected before to and following the conclusion of transport tests was used ( 19 ).…”
Section: Methodsmentioning
confidence: 99%